2022
DOI: 10.1002/advs.202200393
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling Alkali‐Metal‐Assisted Domain Distribution of Quasi‐2D Perovskites for Cascade Energy Transfer toward Efficient Blue Light‐Emitting Diodes

Abstract: Solution processable quasi‐2D (Q‐2D) perovskite materials are emerging as a promising candidate for blue light source in full‐color display applications due to their good color saturation property, high brightness, and spectral tunability. Herein, an efficient energy cascade channel is developed by introducing sodium bromide (NaBr) in phenyl‐butylammonium (PBA)‐containing mixed‐halide Q‐2D perovskites for a blue perovskite light‐emitting diode (PeLED). The incorporation of alkali metal contributes to the nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 54 publications
2
18
0
Order By: Relevance
“…Undoubtedly, the passivation effect could effectively suppress the defect-related nonradiative recombination in the quasi-2D phases, which would further enhance the interphase energy transfer. 34,35 As expected, the rearranged phase distribution of the perovskite films shows an efficient energy transfer from the small-n phases, as deduced from the femtosecond transient absorption spectroscopy (TAS) measurement results shown in Figure 3 and Figure S6. For the perovskite films of R 40 , the photobleaching peaks of the middle-n phases are not distinguishable and the energy transfer occurs from the n = 1 phase to the n = 2 phase and then to the light emission phase, as presented in Figure 3b, which again confirms that the energy transfer gap is really formed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Undoubtedly, the passivation effect could effectively suppress the defect-related nonradiative recombination in the quasi-2D phases, which would further enhance the interphase energy transfer. 34,35 As expected, the rearranged phase distribution of the perovskite films shows an efficient energy transfer from the small-n phases, as deduced from the femtosecond transient absorption spectroscopy (TAS) measurement results shown in Figure 3 and Figure S6. For the perovskite films of R 40 , the photobleaching peaks of the middle-n phases are not distinguishable and the energy transfer occurs from the n = 1 phase to the n = 2 phase and then to the light emission phase, as presented in Figure 3b, which again confirms that the energy transfer gap is really formed.…”
mentioning
confidence: 99%
“…This is consistent with the in situ GIWAXS measurement results that DMSO vapor can significantly facilitate the ligand migration and delay the crystallization of ligands, which not only results in the suppressed ligand aggregation effect but also contributes to the passivation effect. Undoubtedly, the passivation effect could effectively suppress the defect-related nonradiative recombination in the quasi-2D phases, which would further enhance the interphase energy transfer. , …”
mentioning
confidence: 99%
“…Several articles have reported that smaller-sized alkali metals improved the efficiency of blue PeLEDs without destroying the original emission spectrum. Cai et al 76 studied the role of NaBr doping in a mixed halide quasi-2D perovskite containing PBA for blue light emission. The NaBr works as the spacer ligand to provide extra modulation of the distribution of quasi-2D perovskite.…”
Section: Alkali Metal Roles In Peledsmentioning
confidence: 99%
“…Additives are usually used for phase composition and defect passivation, thus efficiently improving the performance of PeLEDs. 8,[33][34][35][36][37][38][39][40][41] Organics, such as ethoxylated trimethylolpropane triacrylate (ETPTA) containing CQO functional groups, can passivate defects both on the surface and within the perovskites. These materials are, therefore, great candidates for additives.…”
Section: Organicsmentioning
confidence: 99%